Differences in Leukocyte Telomere Length between Coronary Heart Disease and Normal Population: A Multipopulation Meta-Analysis. (6th May 2019) - Xu, Xiaofeng; Hu, Haochang; Lin, Ying; Huang, Fangzhong; Ji, Huihui; Li, Yin; Lin, Shaoyi; Chen, Xiaomin; Duan, Shiwei
Abstract : Coronary heart disease (CHD) is one of the most common causes of death in the world. Numerous studies have shown that as the degree of atherosclerotic disease increases, leukocyte telomere length gradually decreases. Short telomeres increase the risk of all-cause death and cardiovascular death. However, the reported results are not consistent, since the experimental design method, the measurement method, and the disease outcome are different. Therefore, we searched five major literature databases (Pubmed, Web of science, Embase, CNKI, and Wangfang) and finally included 18 eligible articles (including 5, 150 patients with CHD and 9341 controls). We found that telomere length in patients with CHD was significantly shorter than that in controls, and the telomere length was inversely correlated with the severity of CHD. Subgroup analysis showed that telomere shortening was the most significant in Asian patients with CHD, in CHD patients with an average age <65 years, and in men with CHD. The mechanism of shortening the telomere length leading to the occurrence and development of CHD is worthy of further study.